-30+5(x-2)=4x+7

Simple and best practice solution for -30+5(x-2)=4x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -30+5(x-2)=4x+7 equation:


Simplifying
-30 + 5(x + -2) = 4x + 7

Reorder the terms:
-30 + 5(-2 + x) = 4x + 7
-30 + (-2 * 5 + x * 5) = 4x + 7
-30 + (-10 + 5x) = 4x + 7

Combine like terms: -30 + -10 = -40
-40 + 5x = 4x + 7

Reorder the terms:
-40 + 5x = 7 + 4x

Solving
-40 + 5x = 7 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-40 + 5x + -4x = 7 + 4x + -4x

Combine like terms: 5x + -4x = 1x
-40 + 1x = 7 + 4x + -4x

Combine like terms: 4x + -4x = 0
-40 + 1x = 7 + 0
-40 + 1x = 7

Add '40' to each side of the equation.
-40 + 40 + 1x = 7 + 40

Combine like terms: -40 + 40 = 0
0 + 1x = 7 + 40
1x = 7 + 40

Combine like terms: 7 + 40 = 47
1x = 47

Divide each side by '1'.
x = 47

Simplifying
x = 47

See similar equations:

| 9-7x=42+(-4x) | | 3x^2-58x-40=0 | | 3ab-2b=3a-b | | -3x^2-3x+90=0 | | 1.2y-0.3x=0.12 | | -7x-5y=11 | | X/11=-22 | | f(x)=2x^2-16x+27 | | 3Y-9-3Y=-9 | | 1.2x-0.3y=0.12 | | 12-7x=9x-5x-87 | | 4x^3+72x^2+68x=0 | | 5/6-x/6=6/5 | | 2^3*x=1/64 | | 3x-5x+4-x+7=88 | | -3x+8=5x-2 | | -x^3+10x^2+39x=0 | | 3x-7=3(x-3)+3 | | ln(x+5)=ln(x-4)-ln(x+4) | | a-1/2=2a-2/3 | | 4x+15x+6=3x-14 | | 19+20m+m^2= | | 24x+8x^2+2x^3=0 | | .4w-.3w+.4w=3 | | 3(2x-5)=5(x-4+x) | | 9c^3+12c^2=0 | | 4x^3-48x^2+140x=0 | | 100/10= | | 5(7x+1)=320 | | 3x+2x+3+5x-13=180 | | 2c+4d=8 | | 45m-90=90m |

Equations solver categories